EKSTRAKURIKULER OLAHRAGA DITINJAU DARI KEBUTUHAN STAKEHOLDER PENDIDIKAN - rahmadi rahmadi (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2014)
Extracurricular Sports Judging by Stakeholders Educational Needs. This study aims to provide information for policy makers, especially in the identification and selection of sports organized by the school in extracurricular programs. This research was conducted in three districts/cities Banjarbaru, Superior of the South River, and the Upper Middle River with each of the two secondary undergraduate schools are the most active extracurricular activities.The method used in the study is an evaluation method which is the reactive model:1) identify fireplace, 2) gather information, 3) accountability for results, and 4) recommendations. The data source is represented by the stakeholders education learners, communities, managers and government agencies Education and Culture staff represented.The results showed that there was a common perception among stakeholders that the program is implemented in extracurricular sports activities at school has not met the needs of the community, especially for students. It is expected that schools may review the policy on extracurricular programs are implemented. Keywords: Policy, extracurricular sports, needs assessment